Effect of Time and Temperature on TPC Parameters in WIP Products Dry Marination Process of Chicken Fillet - Dhita Sari Siregar; Yeni Kurniati; Amelya Setyawati; Gita mutiara Annisa Chaerani; Tri Matya Ningrum; Palupi Purnhama Dewi; Febby Barita Lumban Tobing; Khoirunnisa Rahmah Shadrina (Universitas Kristen Cipta Wacana, 2026)
Work in Process (WIP) dry-marinated chicken fillet is a semi-finished product that remains highly susceptible to microbial contamination before the cooking stage. Inadequate control of storage time and temperature during WIP handling may accelerate bacterial growth, thereby reducing product quality and compromising food safety. This study aimed to evaluate the effects of storage time and temperature on the Total Plate Count (TPC) of dry-marinated chicken fillet during the WIP stage. The study employed an experimental design by storing dry-marinated chicken fillets under different storage temperatures and holding times. Total Plate Count analysis was conducted using the standard pour plate method, and the obtained data were analyzed using analysis of variance (ANOVA) to determine the significance of treatment effects. The results demonstrated that both storage time and temperature significantly affected (P < 0.05) the TPC values. Increasing storage duration consistently increased bacterial populations, while higher storage temperatures accelerated microbial proliferation compared with refrigerated storage. The interaction between storage time and temperature indicated that improper WIP handling substantially increased the microbiological risk before the cooking process. Although dry marination may contribute to slowing bacterial growth through reduced water activity and antimicrobial effects of seasoning ingredients, these effects were insufficient to inhibit microbial proliferation during prolonged storage. Therefore, maintaining refrigerated storage and minimizing WIP holding time are essential to preserve microbiological quality and ensure compliance with food safety standards. These findings provide practical recommendations for optimizing WIP handling procedures and strengthening Hazard Analysis and Critical Control Point (HACCP)-based quality management in poultry processing industries.